Indigenous entrepreneurship sustainability in Malaysia - Nor Emmy Shuhada, Derani; Mazita, Mokhtar; Wan Noordiana, Wan Hanafi (GBMR, 2020)
The government of Malaysia endorsed the Eleventh Malaysia Plan aimed to be developed county in the numerous crucial dimensions including economics, political, social, spiritual, psychological and also cultural. The government of Malaysia underpin efforts to help cultivate all level of people including the Orang Asli communities. One of the initiatives by the government is through entrepreneurship where entrepreneurship increase job creation as well as economic growth. Nevertheless, the business or product produce by the Orang Asli entrepreneurs in Malaysia are often non-permanent, constant and sustained despite various initiatives commenced by the government. Therefore, this study aims to propose conceptual framework using the theory of planned behavior to capture a reasonable way for the Orang Asli to sustain their business. Moreover, this study aims to determine whether the value placed in the theory of planned behavior affects the level of entrepreneurial intention among the Orang Asli. Therefore, the insight into the factors of sustainable entrepreneurship can be an essential step towards designing a practical and durable policy mechanism for the implementation of the theory of planned behavior when developing entrepreneurial initiatives or programs to the Orang Asli communities. Results from this paper will be conducted using survey method, adapted questionnaire as the main instrument. A total of 150 indigenous from the Pahang, Perak and Selangor state will be selected as respondents. To analyze the results descriptive analysis will use including reliability and validity test using Cronbach Alpha and the relationships between independent variables and dependent variables will be tested using Pearson Correlation